Survey and characterization of pathogenic and mycotoxigenic microorganisms in walnut (Juglans regia L.) - Magris, Gina (2024)
Walnut (Juglans regia L.) is the most important nut crop in Argentina, with a cultivated area of about sixteen thousand hectares. The quality and safety of walnut production can be affected by phytopathogenic bacteria and/or mycotoxinproducing fungi. This study sought to explore the incidence of such microorganisms in a walnut plantation in Belén, a department in the province of Catamarca. Fallen fruit showed stylar end necrosis that extended towards the inner tissues and reached the kernel. These symptoms were consistent with those described for brown apical necrosis (BAN). Ten symptomatic fruits from each orchard in the plantation were disinfected with sodium hypochlorite (1% v/v) for 2 min and rinsed with sterile distilled water. Small pieces of affected tissue were excised and plated on potato dextrose agar (PDA) supplemented with streptomycin (200 mg/l). After 7 days, fungal species were isolated and identified on the basis of conidial morphology and through molecular techniques. The DNA of a selected strain named H1 was extracted, and internal transcribed spacer (ITS) regions were amplified and sequenced. A BLAST analysis of the isolate’s nucleotide sequences indicated a 97-100% similarity with reference sequences of Alternaria alternata in GenBank. Its pathogenicity was studied by inoculating a 10-μl droplet of a conidial suspension (1 × 106 conidia/ml) on the stigmatic end of walnuts. All the inoculated fruits developed apical necrosis. To validate Koch’s postulates, symptomatic tissuefrom the inoculated fruits was plated on PDA, and H1 was successfully reisolated. A Gram-negative bacterial strain was also isolated and named XVM1. It was characterized at the morphological and biochemical level, and identified as a Pantoea sp. through 16S rDNA gene sequencing and fatty acid profiling (FAMEs). These results were corroborated by MALDI-TOF MS. As with H1, walnut fruits inoculated with this bacterial strain developed characteristic BAN symptoms. To further complement all these findings, walnut-associated mycoflora was studied in the same region.Sixty-one percent of the isolated strains were identified as potential mycotoxin producers, with a high incidence of the genera Aspergillus, Alternaria, and Penicillium. Although species belonging to Aspergillus section Flavi were the most frequently isolated, low levels of aflatoxins were detected (4.4 ng/g for AFB1). The presence of BAN and aflatoxins in a commercial walnut plantation in Argentina suggests a need for improved phytosanitary control programs. Nevertheless, given the limited scope of the data presented here, epidemiological studies should be conducted to betterunderstand the impact of the disease on walnut production in Argentina.